KONSEP PENJARA ISLAM: TINJAUAN AKTIVITI INSTITUSI PENJARA DAN PENGALAMAN PARA BANDUAN DI PENJARA MALAYSIA - Yusof, Abdullah (Jurnal Syariah, 2019)
The article aims to analyse the position of prison according to Islamic perspective. It discusses the concept ofprison in Islam and then compares it with prisons in Malaysia. It is found that such activities conducted in Malaysia’s prison are in disagreement with Islam.